Outcome of Arthroscopic Rotator Cuff Repair at Maharaj Nakorn Chiang Mai Hospital: A Review of the Surgery Results - Phornphutkul, Chanakarn; Rajchaweang, Korakod; Bangkhen, Watanachai; Luevitoonvechkij, Sirichai (Biomedical Sciences and Clinical Medicine, 2024)
Objective To review results the of arthroscopic rotator cuff repair at Maharaj Nakorn Chiang Mai Hospital. Methods Forty two patients, with a median age of 57.2 years, were evaluated for daytime and nighttime pain by using the VAS score after undergoing arthroscopic rotator cuff repair with a follow up period of more than 6 months. Range of motion was recorded before and after surgery to evaluate the result. Subjective and functional outcomes were assessed by using the Simple Shoulder Test (SST) and UCLA score. Patients were interviewed also for their satisfaction of the surgery results. Results The VAS score for daytime pain reduced significantly from 7.35 to 0.92. Forward elevation significantly improved from 136.79O to 171.31O, postoperatively. Abduction also improved from 117.74O to 166.45O after surgery. The mean UCLA and SST score was 29.33 and 9.55, respectively at six months. When using the criterion of UCLA score ≥ 27, 80.90% of the patients were classified as having good to excellent results. After 6 months, all of the patients (100%) were satisfied with the results of surgery. Conclusion All endoscopic rotator cuff repair at Maharaj Nakorn Chiang Mai Hospital had favorable outcomes with comparable results to other series. Due to its advantageous ability to assess the articular pathology, improve rotator cuff release, improve visualization of subacromion space, and create faster recovery compared to the conventional open technique, this method should become one of the standard treatments of rotator cuff conditions.